FOR THE EDUCATION OF THE COSMOPOLITAN. THE CASE OF TAGORE AND THE GLOBALIZED SELF - Pappas, Georgios (Educological discourse, 2020)
The phenomenon of globalization creates a variety of tensions and dilemmas. The present paper attempts to approximate this phenomenon by tracing the different trends arising from the corresponding descriptive, evaluative and regulatory judgments. In addition, the various philosophers' views on the dialogue on cosmopolitanism and patriotism are outlined, and Tagore's reflections and positions on cosmopolitanism and ecumenical education are highlighted, with emphasis on the development of critical thinking and constructive dialogue. The debate on globalization raises concerns and dilemmas in educational theory as well, with the consequent urgency of the need for rapid adaptation to the challenging environment. The conclusion drawn from the presentation of the aforementioned positions is the need for the implementation of educational policies that will be based on education for empathy, solidarity and intercultural respect. Revisiting the commitment to culture within a universal horizon based on acceptance of diversity requires the existence of strategic planning that contains actions and choices that make it flexible and efficient.